OF BORDERS AND BODIES: A DISSECTION OF GENDER ROLES - V S, Krishnapriya; N, Sreelakshmi (International Journal of Psychosocial Rehabilitation, 2020)
There is no original or primary gender a drag imitates, but gender is a kind of imitation for which there is no original”Judith ButlerThe delicate borders between sexuality and gender roles were always a conundrum. The obvious social constructs that limit a man and a woman into consignments were always the manipulation of the society. The society assigns certain attributes to a male and those who deviate from the pattern is de-masculinised. Same is the case of women. An individual is always conditioned by these gender social constructs. This paper explores these gender social borders through the play Dance like a Man by Mahesh Dattani using Social Role theory. It examines the hypocrisy within the precincts of the family, woman acting as betrayer of her own sex to facilitate male pre-eminence in Indian family, social prejudice against non-conforming professions like dance, trinity of patriarchy, capitalism, and how political power join forces together against the existence of a girl and the clash between tradition and modernism